2017
DOI: 10.3892/etm.2017.4953
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the hemodynamics and right ventricular function in pulmonary hypertension by echocardiography compared with right-sided heart catheterization

Abstract: The present study aimed to evaluate hemodynamics and right ventricular function in patients with pulmonary hypertension (PH) using transthoracic echocardiography and to compare these results with measurements obtained using right-sided heart catheterization (RHC). A total of 75 patients with PH were examined using echocardiography and RHC. Patients were divided into the following two groups according to their difference between SPAPecho and SPAPRHC measurement: The overestimated group and underestimated group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…As the most well-adopted approach in PH screening, sPAP ECHO has also been shown to be a reliable method [ 3 ]; however, it has not yet been examined whether sPAP ECHO is superior to other parameters in determining the probability of PH. sPAP ECHO can also provide valuable information for evaluating treatment response and even predicting prognosis [ 4 , 5 ]; however, there is still a high proportion of overestimation or underestimation of sPAP ECHO [ 6 ]. To evaluate PH patients’ condition appropriately and avoid too invasive examination, we need to understand situations in which sPAP ECHO is under/overestimated.…”
Section: Introductionmentioning
confidence: 99%
“…As the most well-adopted approach in PH screening, sPAP ECHO has also been shown to be a reliable method [ 3 ]; however, it has not yet been examined whether sPAP ECHO is superior to other parameters in determining the probability of PH. sPAP ECHO can also provide valuable information for evaluating treatment response and even predicting prognosis [ 4 , 5 ]; however, there is still a high proportion of overestimation or underestimation of sPAP ECHO [ 6 ]. To evaluate PH patients’ condition appropriately and avoid too invasive examination, we need to understand situations in which sPAP ECHO is under/overestimated.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, sPAP ECHO can also provide valuable information in evaluating treatment response and even predicting prognosis [2,3] . But high proportion of overestimation or underestimation of sPAP ECHO still remained [4] . As previous studies showed, TR severity, TR signal quality, the level of pulmonary artery systolic pressure and right ventricular function would affect the accuracy of sPAP ECHO [5][6][7] .…”
Section: Introductionmentioning
confidence: 98%
“…Especially for the latter, the volume of tricuspid regurgitation (TR), the operator’s measurement technique [e.g., taking multiple views to obtain the optimal window, ensuring the maximal continuous-wave (CW) Doppler velocity to flow angle is correctly aligned ( 19 ) and avoiding eccentric jets ( 6 ), over-gaining and artifacts ( 20 ), etc. ], and the patient’s own conditions [e.g., age, sex, body mass index (BMI), breathing, heart rate, cardiopulmonary and metabolic comorbidities, and the ability to change position during examination ( 1 , 21 - 24 ), etc.] all influence the sharpness of the spectral image.…”
Section: Introductionmentioning
confidence: 99%